Video media is more effective to improve balanced nutrition knowledge - Asmi, A. Syamsinar; Tyarini, Indrawati Aris; Saputra, M. Khalid Fredy; Putra, Jaimin Adi; Son, Hae Kyoung (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2024)
Introduction: Providing appropriate nutrition information is important to increase public knowledge about balanced nutrition. One proven effective method is using video media as a means of education. Objective: Analyze the effectiveness of video media in increasing knowledge about balanced nutrition. Methods: This study uses a quasi-experimental study design without group controls. The population of this study is all students, with a sample of 52 people who meet the inclusion and exclusion criteria. The sampling technique used stratified random sampling. Result: The study showed that the use of video increased the average knowledge score (mean) by 85.96 video (p=0.003). This study shows that providing nutrition education with video media is more effective in increasing balanced nutrition knowledge. Conclusion: Video media has been proven more effective in increasing knowledge about balanced nutrition. Video media can present information more interesting, interactive, and visually, making it easier for the audience to understand and remember the material conveyed. A significant increase in knowledge in the group receiving the video media intervention showed that this method is an effective educational tool in balanced nutrition campaigns. Therefore, video media is recommended as a nutrition counseling strategy to expand the reach and impact of health education in the community.